Motor, memory, and anxiety-like behavioral impairments associated with brain-derived neurotrophic factor and dopaminergic imbalance after inhalational exposure to deltamethrin - Marina F. Souza; Katty A.A.L. Medeiros; Lívia C.R.F. Lins; José M.M. Bispo; Auderlan M. Gois; Edson R. Santos; Thiago H. Almeida-Souza; João E.C. Melo; Heitor S. Franco; Rodolfo S. Silva; Eduardo A. Pereira-Filho; Marco Aurelio M. Freire; et al. (Brain Research Bulletin, 2022)
Believed to cause damage to the nervous system and possibly being associated with neurodegenerative diseases, deltamethrin (DM) is a type II pyrethroid used in pest control, public health, home environment, and vector control. The objective of this study was to evaluate the motor, cognitive and emotional changes associated with dopaminergic and BDNF imbalance after DM exposure in rats. Sixty Wistar rats (9–10 months-old) were used, under Ethics Committee on Animal Research license (ID 19/2017). The animals were randomly divided into four groups: control (CTL, 0.9% saline), DM2 (2 mg DM in 1.6 mL 0.9% saline), DM4 (4 mg of DM in 1.6 mL of 0.9% saline), and DM8 (8 mg of DM in 1.6 mL of 0.9% saline). DM groups were submitted to 9 or 15 inhalations, one every 48 h. Half of the animals from each group were randomly selected and perfused 24 h after the 9th or 15th inhalation. Throughout the experiment, the animal’s behavior were evaluated using catalepsy test, open field, hole-board test, Modified Elevated Plus Maze, and social interaction. At the end of the experiments, the rats were perfused transcardially and their brains were processed for Tyrosine Hydroxylase (TH) and Brain derived neurotrophic factor (BDNF) immunohistochemistries. The animals submitted to 9 inhalations of DM showed a reduction in immunoreactivity for TH in the Substantia nigra pars compacta (SNpc), ventral tegmental area (VTA), and dorsal striatum (DS) areas, and an increase in BDNF in the DS and CA1, CA3 and dentate gyrus (DG) hippocampal areas. Conversely, the animals submitted to 15 inhalations of DM showed immunoreactivity reduced for TH in the SNpc and VTA, and an increase in BDNF in the hippocampal areas (CA3 and DG). Our results indicate that the DM inhalation at different periods induce motor and cognitive impairments in rats. Such alterations were accompanied by dopaminergic system damage and a possible dysfunction on synaptic plasticity.